Incorporación de los Key Audit Matters en las actividades de auditoría: una revisión documental (2021)
For the development of this paper, a documentary review was carried out that would serve as input to analyze the need that arises from the IAASB to implement the International Standard on Auditing (ISA) 701, related to Key Audit Matters (KAMs) and present the state of the art of the research that has been conducted regarding the effects of KAMs in audit reports. At the same time, it seeks to present how Colombian regulations have progressed regarding the implementation of ISA 701, which addresses this issue. Among the main results of this research, it is highlighted that the effects of KAMs can vary between countries and even between industries, which means that the results of the analyzed studies are not homogeneous. However, it follows that KAMs can bring informative value at a general level for information users, since all auditors of listed companies, regardless of their field of work, should present the issues that, in their professional judgment, required greater attention to the work carried out.